Impact of Agri-Value Chains on Employment and Income Generation - Baboo, Bangali (Indian Farming, 2015)
The greatest impact brought by the NAIP has been that of creating entrepreneurship in Indian agriculture. This has benefited all the stakeholders be it farmers, traders, processors or consumers. Moreover, a value-chain approach has brought about creation of employment and income generation.